Jim Crow America : a documentary history - Lewis, Catherine M.; Lewis, J. Richard, 1967- (University of Arkansas Press, 2009)
This is a resource on racism and segregation in American life. The book is chronologically organized into five sections, each of which focuses on a different historical period in the story of Jim Crow: inventing, building, living, resisting, and dismantling.